Integrated Approaches in Complex Agro: A Comprehensive Review of Agricultural, Livestock and Fisheries Research - Wardani, Mastan Sri; Yasin, Khotifah (Professorline, 2024)
An integrated approach in the agro complex integrates the agriculture, livestock, and fisheries sectors to create a more efficient and sustainable food production system. This article presents a comprehensive review of current research in these three sectors, focusing on integration and synergies between sectors. The methodology includes systematic analysis of scientific literature, case studies, and empirical data from various regions. Research in the agricultural sector shows increased productivity through precision technology and agroecological practices. Crop-livestock integration increases land and resource use efficiency. The livestock sector focuses on environmentally friendly production systems and animal welfare, with innovations in nutrition and health management. The fisheries sector is facing the challenge of managing aquatic resources, with research into sustainable aquaculture and selective fishing techniques. An integrated approach facilitates the exchange of nutrients and energy between sectors, reduces waste, and increases resource efficiency. However, its implementation faces challenges such as management complexity and high investment requirements. Further research is needed to optimize integration, develop viable business models, and evaluate long-term impacts. In conclusion, an integrated approach in agro-complexes offers potential solutions to increase the resilience and sustainability of the global food system. Cross-disciplinary collaboration and policy support are needed to accelerate the adoption and development of this approach at multiple scales.